PREVALENSI KONTAMINASI BAKTERI Salmonella sp. DAN Shigella sp. PADA DAGING AYAM POTONG YANG DIJUAL OLEH PEDAGANG PASAR TRADISIONAL DI KOTA DENPASAR - Surya Putra, I Gusti Agung Utama; Darwinata, Agus Eka; Putra Pinatih, Komang Januartha; Fatmawati, Ni Nengah Dwi (Universitas Udayana, 2022)
Salmonella sp. and Shigella sp. are bacterias that have become the most frequent cause of foodborne illness in developing countries. One of its contamination is chicken meat which is a daily staple food. The contamination occurs if the processing, storage, and distribution of chicken meat are improper. The aim of this study was to find the prevalence of contamination by Salmonella sp. and Shigella sp. on chicken meat sold by traditional market traders in Denpasar City. The type of research is cross-sectional research with descriptive observational. This study used the cluster sampling method. The total of samples is 24 samples and were taken from six traditional markets in each district of Denpasar City. Identification of Salmonella sp. and Shigella sp.Bacteria was done at the Integrated Biomedical Laboratory of Medical Faculty of Udayana with the culture method on Salmonella-Shigella agar media and Simmons Citrate culture. The total percentage contamination of Salmonella sp. was 58.33% (14/24), while Shigella sp. 20.83% (5/24). This bacterial contamination is caused by the lack of attention to hygiene in every chicken meat processing, storage, and distribution. The researcher suggests that further similar research be carried out using advanced identification methods to distinguish bacterial colonies in more detail and conduct a quantitative assessment of environmental contamination where chicken traders live.